Statistically derived factors of varied importance to audiologists when making a hearing aid brand preference decision. - Johnson EE; Mueller HG; Ricketts TA (Journal of the American Academy of Audiology, 2009)
Purpose: To determine the amount of importance audiologists place on various items related to their selection of a preferred hearing aid brand manufacturer.Research Design: Three hundred forty-three hearing aid-dispensing audiologists rated a total of 32 randomized items by survey methodology.Results: Principle component analysis identified seven orthogonal statistical factors of importance. In rank order, these factors were Aptitude of the Brand, Image, Cost, Sales and Speed of Delivery, Exposure, Colleague Recommendations, and Contracts and Incentives. While it was hypothesized that differences among audiologists in the importance ratings of these factors would dictate their preference for a given brand, that was not our finding. Specifically, mean ratings for the six most important factors did not differ among audiologists preferring different brands. A statistically significant difference among audiologists preferring different brands was present, however, for one factor: Contracts and Incentives. Its assigned importance, though, was always lower than that for the other six factors.Conclusions: Although most audiologists have a preferred hearing aid brand, differences in the perceived importance of common factors attributed to brands do not largely determine preference for a particular brand.